ANALISIS PERSEPSI KONSUMEN TERHADAP KONSEP DUAL BANKING SYSTEM DAN PENERAPAN KONSEP SYARIAH DI BANK SYARIAH MANDIRI YOGYAKARTA - , Defika Hanum Permatasari ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Characteristics of the dual banking system ( conventional and Islamic ) can affect different consumers as potential clients in determining their preference to conventional banking or Islamic banking . The purpose of this study are to determine consumer perceptions of dual banking options ( conventional and Islamic ) in the use of banking services, to determine customers' awareness and attitude towards dual banking system with Islamic concepts , to determine the type and character of our customers choose what kind of Islamic banks , for know the relationship and linkages between respondent characteristics (sex , age , occupation , big spending per month , last education , frequency of visits , type of deposit , the facilities are used ) to the preference option to Bank Syariah Mandiri, and to determine the relationship and linkage relationships and linkages Consumer perceptions between the Marketing Mix (4 P's , Product, Price , Place , Promotion) . The population was Bank Syariah Mandiri customers sampling technique used in this study was purposive sampling . This study is a descriptive exploratory study . Method of data analysis used in this study is crosstab and chi square . The analysis showed that the majority of respondents have a very good perception of the dual banking system ( conventional and Islamic ) in the use of banking services , as many as 114 people ( 57 % ) , the majority of survey respondents have a relatively good awareness of the dual banking system with the concept of syariah , as many as 96 people ( 48 % ) and the majority of respondents have a relatively good attitude to the dual banking system with this concept , as many as 120 people ( 60 % ) . Results crosstab and chi square analyzes showed that perception , awareness and attitude of the dual banking system with Islamic concept positively and significantly related to the components of Bank Syariah Mandiri marketing mix ( Product, Price , Place , and Promotion )